Identifikasi dan Benchmarking Faktor Penghalang Implementasi Konsep Lean Construction pada Megaproyek di Indonesia dengan Metode MICMAC - Ian Isman Irfandi; Farida Rachmawati (Jurnal Aplikasi Teknik Sipil, 2023)
Megaprojects have very high complexity because they are interconnected with several functions and organizations currently, many megaprojects have poor performance in terms of quality management which results in productivity and quality of work. Waste in the construction sector in Indonesia is quite large, namely 57% when compared to the manufacturing industry which is only 26%, one of the concepts that can be adapted from the manufacturing industry is the lean concept. This study aims to identify the inhibiting factors in the implementation of the lean construction concept in megaprojects in Indonesia. Factor identification is carried out by collecting factors from previous research and distributing questionnaires to practitioners and respondents who are directly involved in project construction, which is then classified or benchmarked to find the fundamental factors in implementing the concept of lean construction in megaprojects in Indonesia. The method for classifying factors in this study is Matrices Impacts Cruise's Multiplication Appliquee a UN Classement (MICMAC) where benchmarking is carried out based on driving power and dependent power, which in this study obtained 2 clusters namely driving power and linkage for barrier factors.